2018
DOI: 10.1029/2018ef000822
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Trends of Anthropogenic SO2, NOx, CO, and NMVOCs Emissions in China

Abstract: Studies reporting the historical trends of SO 2 , NO x , CO, and nonmethane volatile organic compounds emissions in China using unified approaches and sources are limited. Here we established 66-year emission trends of these four species in China. Six primary anthropogenic sources were included, and we made a series of improvements to the few existing inventories based on detailed statistical data, recently published emission factors, and technology renewal to reduce the uncertainties. National SO 2 , NO x , C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
92
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(115 citation statements)
references
References 61 publications
7
92
0
Order By: Relevance
“…γ NO 3 is taken to be 1 × 10 −3 following Jacob (2000). γ NO 2 for the hydrolysis Reaction (R11) is de- creased from 1 × 10 −4 (Jacob, 2000) to 1 × 10 −5 on the basis of laboratory measurements (Bröske et al, 2003;Stemmler et al, 2007;Tan et al, 2016). This decrease in γ NO 2 yields a 24 h mean wintertime HONO/NO 2 molar concentration ratio of 0.035 over eastern China in GEOS-Chem, consistent with the observed range of 0.015-0.071 (Hendrick et al, 2014;Spataro et al, 2013;Wang et al, 2017Wang et al, , 2013.…”
Section: Geos-chem Modelsupporting
confidence: 76%
“…γ NO 3 is taken to be 1 × 10 −3 following Jacob (2000). γ NO 2 for the hydrolysis Reaction (R11) is de- creased from 1 × 10 −4 (Jacob, 2000) to 1 × 10 −5 on the basis of laboratory measurements (Bröske et al, 2003;Stemmler et al, 2007;Tan et al, 2016). This decrease in γ NO 2 yields a 24 h mean wintertime HONO/NO 2 molar concentration ratio of 0.035 over eastern China in GEOS-Chem, consistent with the observed range of 0.015-0.071 (Hendrick et al, 2014;Spataro et al, 2013;Wang et al, 2017Wang et al, , 2013.…”
Section: Geos-chem Modelsupporting
confidence: 76%
“…These observations have been qualitatively consistent with the 35 trends in Chinese NOx emission inventories, showing an increasing trend of NO2 columns over China between 1994 and and a sharp reversal in eastern China since 2011 (Richter et al, 2005;van der A et al, 2006, 2008Krotkov et al, 2016;Schneider et al, 2015;Duncan et al, 2016;Cui et al, 2016). However, the trends in the NO2 columns are steeper than in the emission inventories (Zhang et al, 2007;Stavrakou et al, 2008;Zhang et al, 2012b;Hilboll et al, 2013;Liu et al, 2017;Zheng et al, 2018). For example, Zhang et al (2007) found that NO2 columns over China increased two-fold from 1996 40 to 2004 while their emission inventory reported a 60% increase.…”
mentioning
confidence: 98%
“…Since then, China has adopted strong measures to decrease air pollution by setting stringent emissions standards, capping coal use, increasing vehicle fuel efficiency, closing outdated facilities, and growing renewable energy 30 Zheng et al, 2018). Bottom-up inventories estimate that China's NOx emissions decreased by 20% between 2011 and 2017, despite continuing economic expansion Zheng et al, 2018). There is a strong need to evaluate these emission inventories and their trends for air quality management.…”
mentioning
confidence: 99%
“…In fact, the scenario discussed above may have already happened. Recent studies have indicated that SO 2 emissions in China have decreased since 2005 (Li et al, ; Sun et al, ), which significantly contributed to the decline in global SO 2 emissions (Klimont et al, ). Furthermore, Zhao et al () found that the JA mean UTT in East Asia exhibited a significant increasing trend and that the EASM circulation was intensified at the beginning of the 21st century using the NCEP‐NCAR reanalysis data set from 1951 to 2013.…”
Section: Resultsmentioning
confidence: 99%